2020
DOI: 10.1177/0146167220941294
|View full text |Cite
|
Sign up to set email alerts
|

Change Appeals: How Referencing Change Boosts Curiosity and Promotes Persuasion

Abstract: Does merely referencing that an object or entity has changed affect people’s attitudes and intentions toward it? This research investigates the possibility that change references spark curiosity and information seeking, which can have a positive or negative effect on people’s evaluations of a target stimulus, depending on the information environment. Seven experiments reveal that referencing that an object or entity has changed decreases perceptions of its longevity, but also sparks curiosity about it—a desire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…People tend to evaluate an object or a practice more positively when the object/practice has existed for a longer duration, even when duration is unrelated to quality (Eidelman et al, 2010;Kupor et al, 2021).…”
Section: Duration (Of Existence)mentioning
confidence: 99%
See 1 more Smart Citation
“…People tend to evaluate an object or a practice more positively when the object/practice has existed for a longer duration, even when duration is unrelated to quality (Eidelman et al, 2010;Kupor et al, 2021).…”
Section: Duration (Of Existence)mentioning
confidence: 99%
“…People tend to evaluate an object or a practice more positively when the object/practice has existed for a longer duration, even when duration is unrelated to quality (Eidelman et al, 2010; Kupor et al, 2021). For example, in one study by Eidelman et al (2010), participants viewed a relatively unknown painting and judged its aesthetics.…”
Section: Review Integration and Predictionmentioning
confidence: 99%
“…This curiosity, in turn, could raise involvement and deepen message processing. Indeed, recent research suggests that curiosity stimulates information seeking and message processing in persuasion contexts, which can amplify the impact of a persuasive message (Kupor et al, in press; Kupor & Tormala, 2015). Although past research is clear in suggesting that feelings of involvement and consequent information processing help drive at least some acts of receptiveness in persuasion, a complete articulation of the reasons why (e.g., surprise, curiosity, or another intermediate mechanism) awaits further research.…”
Section: A Closer Look At Mechanismmentioning
confidence: 99%
“…These analyses replicated past work 53,54,55 , which has found that film engagement and awareness of bias encouraged participants to learn more about issues surrounding unfair treatment and biases. Moreover, as mentioned in the introduction, engaging with new information can further influence attitudes and beliefs 56,57 and behaviours 58,59,60 . Thus, in secondary analyses, we examined whether seeking out additional information after "Picture a Scientist" would lead to further positive actions and a stronger awareness of gender bias.…”
Section: Studymentioning
confidence: 99%
“…Moreover, a film that forces viewers to reflect on their personal biases may also motivate them to find resources to help address their bias 54,55 . Critically, acquiring new information about a topic ultimately shapes people's attitudes and beliefs 56,57 and changes behaviours 58,59,60 . Thus, engaging with entertaining media has the potential to encourage viewers to continue acquiring new information and learning about bias and mistreatment.…”
Section: Introductionmentioning
confidence: 99%